A single‐center experience with undifferentiated embryonal sarcoma of the liver. Issue 12 (18th July 2016) - Mathias, Melissa D.; Ambati, Srikanth R.; Chou, Alexander J.; Slotkin, Emily K.; Wexler, Leonard H.; Meyers, Paul A.; Magnan, Heather
Abstract: Undifferentiated embryonal sarcoma of the liver (UESL) is a rare aggressive mesenchymal pediatric tumor. Previously, reported outcomes have been very poor. Here, we report a single‐center experience of five patients with UESL treated with upfront gross total resection and adjuvant chemotherapy. We have a median follow‐up of 8 years with a range from 5 to 19 years with 100% event‐free survival.